2021
DOI: 10.1177/1056789521991873
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high temperature on the mechanical behavior of calcium silicate hydrate under uniaxial tension and compression

Abstract: When subjected to high temperatures, cement-based materials can dehydrate, which, in turn, affects the mechanical property of the main binding phase (calcium silicate hydrate) at the atomic scale. However, the effects of high temperature on the tensile and compressive behavior of calcium silicate hydrate (C−S−H) grains under uniaxial loading remains poorly understood. In this work, based on reactive molecular simulations, the tensile strength, compressive strength, and stress-strain relations of C−S−H grains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…Based on previous investigations (Zhang et al, 2020a(Zhang et al, , 2021a, the degradation of concrete mainly appears before 700 C (973.15 K). Therefore, the temperature range considered here is between 300 K and 1000 K. Next, we build the molecular C-S-H models exposed to 500 K, 700 K, 900 K, and 1000 K. Here, interlayer water evaporation is assumed to occur above 378 K (around 105 C).…”
Section: Molecular Modelmentioning
confidence: 91%
See 1 more Smart Citation
“…Based on previous investigations (Zhang et al, 2020a(Zhang et al, , 2021a, the degradation of concrete mainly appears before 700 C (973.15 K). Therefore, the temperature range considered here is between 300 K and 1000 K. Next, we build the molecular C-S-H models exposed to 500 K, 700 K, 900 K, and 1000 K. Here, interlayer water evaporation is assumed to occur above 378 K (around 105 C).…”
Section: Molecular Modelmentioning
confidence: 91%
“…Hou et al (2014a) investigated the mechanical and structural character of C-S-H with different interlayer water content, and they found that lower water content can result in a higher strength and modulus. In addition, the decomposition of the hydroxyl group and water evaporation induced by high temperature can considerably influence the mechanical property of the C-S-H grain (Zhang et al, 2020a(Zhang et al, , 2021a(Zhang et al, , 2021b, and the interlayer water has a primary effect on the cohesive force between solid C-S-H grains and the mechanical property of the C-S-H grain-both at ambient (Hou et al, 2014a(Hou et al, , 2014bManzano et al, 2009;Rivas Murillo et al, 2017;Xin et al, 2017;Zhou and Liang, 2019) and high temperature levels (Bonnaud et al, 2013;DeJong and Ulm, 2007;Li et al, 2017). Furthermore, Yang et al (2021) investigated the effect of the dehydration and dihydroxylation on the evolution of mechanical properties of C-S-H.…”
Section: Introductionmentioning
confidence: 99%
“…Many results have been obtained from cylindrical specimens subjected to uniaxial and conventional triaxial compression (CTC, σ 1 > σ 2 = σ 3 ) tests. These results include complete stress–strain curves of rock obtained using a high-stiffness servo-controlled apparatus (Alejano et al., 2017; Guo et al., 2021; Hudson et al., 1972; Liu et al., 2019; Wawersik and Brace, 1971; Zhang et al., 2021). Macroscale tensile–shear failure modes based on failed specimens have been analyzed (Jiang et al., 2016; Li et al., 2020; Medhurst and Brown, 1998), and the microfailure mechanisms have been explored using scanning electron microscopy (SEM) (Fredrich et al., 1989; Nicolas et al., 2016; Sahouryeh et al., 2002) and optical microscopy (Rodriguez et al., 2016; Shimada and Cho, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…For the size effect, the influences of the slenderness ratio (the length-diameter ratio for cylindrical specimens and height-width ratio for prismatic specimens) and the cross-section size at the same slenderness ratio on rock mechanical properties have been investigated, and some results have been acquired. The size effect significantly affects the strength, deformation, and failure characteristics of rocks (Bažant and Xiang, 1997; Hudson et al., 1972; Khoramishad et al., 2014; Li et al., 2011, 2018; Mogi, 1966; Zhang et al., 2020, 2021; Zhao and He, 2017). However, the cross-sectional shape effect on the results of laboratory tests has not been well studied because of sealing problems caused by prismatic specimens piercing the jackets under confining pressure.…”
Section: Introductionmentioning
confidence: 99%
“…16 C-S-H can be described as a colloidal gel made of nanometric grains (see Figure 1). [17][18][19] The C-S-H grains present a layered structure, wherein water can be present in the interlayer spacing, depending on RH. 17 The presence of water in the interlayer space plays a critical role in governing the microstructure of cement pastes.…”
Section: Introductionmentioning
confidence: 99%